2015
DOI: 10.1073/pnas.1506960112
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of the Stargardt phenotype in Abca4 knockout mice through inhibition of vitamin A dimerization

Abstract: Stargardt disease, an ATP-binding cassette, subfamily A, member 4 (ABCA4)-related retinopathy, is a genetic condition characterized by the accelerated accumulation of lipofuscin in the retinal pigment epithelium, degeneration of the neuroretina, and loss of vision. No approved treatment exists. Here, using a murine model of Stargardt disease, we show that the propensity of vitamin A to dimerize is responsible for triggering the formation of the majority of lipofuscin and transcriptional dysregulation of genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 44 publications
1
57
0
Order By: Relevance
“…It is believed that A2E affects the normal functions of the RPE and is involved in retinal diseases. Strategies designed to inhibit A2E formation for AMD and Stargardt disease by inhibiting key visual cycle enzymes or using deuterated vitamin a (C20-D 3 -Vitamin A), respectively, are in development [16][17][18][19]. Most notably, a phase 2 clinical trial using deuterated vitamin a for Stargardt disease is ongoing [20].…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that A2E affects the normal functions of the RPE and is involved in retinal diseases. Strategies designed to inhibit A2E formation for AMD and Stargardt disease by inhibiting key visual cycle enzymes or using deuterated vitamin a (C20-D 3 -Vitamin A), respectively, are in development [16][17][18][19]. Most notably, a phase 2 clinical trial using deuterated vitamin a for Stargardt disease is ongoing [20].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term, oral administration of ALK-001 to ABCA4 −/− reduced the accumulation of lipofuscin and A2E by 70 and 80%, respectively [109]. Assessment of the retina electric response to light signals (electroretinogram) revealed that ALK-001 treatment prevented the gradual loss of visual function observed in the ABCA4 −/− mouse.…”
Section: Strategies That Prevent De Novo Formation Of Lbsmentioning
confidence: 96%
“…Several interventions for STGD have been proposed, including light deprivation 42 , regulation of Vitamin A 43; 44; 45; 46 , gene-replacement therapy 44 , and human stem cell transplantation. 44; 47 Information about current clinical treatment trials can be accessed at ClinicalTrials.gov.…”
Section: Stargardt Diseasementioning
confidence: 99%